TRANSFORMASI TATA KELOLA PERGURUAN TINGGI BERBASIS TEKNOLOGI: TANTANGAN DAN PELUANG DALAM PENYELENGGARAAN UNIVERSITAS ISLAM MASA DEPAN - Zalisman, Zalisman; Asmidaryani, Asmidaryani; Hariati, Haryuni (Universitas Tribhuwana Tunggadewi, 2024)
The aim of this research is to expose the challenges and opportunities of transformation of technology-based college governance on future Islamic universities. This research method is a library expression. The data sources used include journal articles, books, research reports, conference papers, and policy documents related to digital transformation in higher education. The results of this research are some of the opportunities and challenges in transforming technology-based college governance in future Islamic universities. Technology transformation opportunities in Islamic higher education are, improvement, accessibility of education, flexible and adaptive curricula, administrative efficiency, development of digital resources, and global collaboration.